Chlorpyrifos-induced biochemical changes in Cyprinus carpio: Ameliorative effect of curcumin - Yonar, M. Enis (Academic Press Inc Elsevier Science, 2018)
The aim of this study was to determine protective effects of curcumin on some haematological values and oxidant/antioxidant status in Cyprinus carpio exposed to chlorpyrifos. The fish were exposed to two sublethal concentrations of chlorpyrifos (0.040 and 0.080 mg L), and curcumin (100 mg per kg of fish weight) was simultaneously administered for 14 days. Blood and tissue (liver, kidney, and gill) samples were collected at the end of the experiment and analysed to determine the haematological profile (red blood cell count, white blood cell count, haemoglobin concentration, and haematocrit level) and oxidant/antioxidant status (malondialdehyde level and superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase activities) of the fish. There was a significant decrease in the red blood cell count, the haemoglobin concentration, and the haematocrit level and a increase in the white blood cell count of CPF-treated fish. The results revealed a significant increase in the malondialdehyde levels of the groups that were exposed to CPF. Conversely, the MDA levels were significantly decreased by curcumin. Also, CPF exposure caused a significant increase in the superoxide dismutase and glutathione-S-transferase activities and a significant decrease in the catalase and glutathione peroxidase activities. However, curcumin reversed the superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase activities. In conclusion, this study demonstrated that CPF had a negative effect on the haematological values and the oxidant/antioxidant status of the fish. The simultaneous administration of curcumin was neutralised CPF-induced toxicity.
Keywords: Antioxidants; Chlorpyrifos; Curcumin; Fish; Haematology; Oxidative stress